Analysis of LPG Butane (C4H10) Flow Pattern on Swivel Joint Style 40 Sch 80 Using Ansys Fluent - Irawan, I Putu Redy; Buku, Atus; Siahaya, Yusuf (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2026)
The Style 40 swivel joint is a critical component in industrial LPG piping systems, enabling angular motion while maintaining flow continuity. However, geometric misalignment induced by the hinge mechanism can significantly affect internal flow behavior, leading to pressure losses and velocity redistribution. This study aims to investigate the pressure and velocity characteristics of LPG (butane, C₄H₁₀) flow through a Style 40 swivel joint with a hinge rotation angle of 90° using a Computational Fluid Dynamics (CFD) approach. Numerical simulations were conducted using ANSYS Fluent, employing the realizable k–ε turbulence model. The inlet boundary condition was defined by a uniform velocity of 0.139 m/s, while the outlet was specified as 0 Pa. The results indicate that the maximum pressure occurs at the inlet region, reaching approximately 4.8 × 10⁻² Pa, whereas the minimum pressure at the outlet decreases to about −3.0 × 10⁻² Pa, resulting in a total pressure drop of roughly 7.8 × 10⁻² Pa. The flow velocity increases from approximately 0.06 m/s at the inlet to a peak value of 0.24–0.25 m/s near the outlet, accompanied by the formation of localized secondary flows around the hinge region. These findings demonstrate that the hinge mechanism plays a dominant role in governing local pressure losses and velocity redistribution, providing valuable insights for the design and performance evaluation of swivel joints in LPG piping applications.